ANALISIS KONVERGENSI PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR PASCA KRISIS GLOBAL TAHUN 2008 - Zainuri Zainuri; Agus Lutfhi; M Saleh; Siti Aisyah; M Fathorrazi (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
The convergence of economic growth in East Java has a high disparity between districts/cities. This study aims to analyze the convergence and influencing factors in East Java after the 2008/2009 global crisis. The data used are secondary data sourced from the Central Statistics Agency. The analysis used in this research is least squares analysis. Based on the results of the convergence analysis, it is shown that in 2008 after the global crisis, there was sigma convergence in the districts/cities in East Java. However, there is absolute beta convergence in the districts/cities in East Java where there is an influence between the GRDP of the previous year and the GRDP of the following year. There is a conditional beta convergence where the HDI variable has a significant positive effect, the population has a significant negative effect, and the workforce has a significant positive effect on economic growth.